Backlog Reduction in Housing Provision Process using Mixed Approach of DMAIC, SMART and AHP Methodologies - Hermawan, Pri; Sari, Fiana Amanda (Jurnal Manajemen Teknologi, 2017)
Abstract. To support its oil operation, IEC manages four camps which most of its facilities require significant repair, especially its housing complexes. Vacant houses with good condition only available in very limited numbers and were not enough to fulfill all housing requests. In the same time, recent business environment forced company to reduce operational expenditure in building maintenance. Limited numbers of vacant houses, limited budget for building maintenance and higher number of housing requests have created a long waiting list and high backlogs in housing assignment list. This research objective is to analyze the existing process of housing provision which has high backlogs in housing assignment list and to propose the intervention to improve it. Combination of DMAIC (Define, Measure, Analyze, Improve, Control) and Decision Analysis methodologies will be used to explore and solve the issue. Based on the analysis performed, root causes of this problem are no proper prioritization tools in place, no dedicated personnel to enable the task, and outdated policy. Hence, the proposed solutions to solve the problem are: prioritization tools are developed and improved for housing renovation and housing assignment processes, dedicated person is assigned to manage housing provision process and internal housing policy is revised and updated. As the result, with strong support from Leadership and collaboration between cross-functional team, the backlogs in housing assignment list can be reduced to 0 (zero). However, improvement in housing renovation process is still needed, especially in reducing cycle time in perform renovation task.Keywords: DMAIC, Decision analysis, SMART, AHP, housing provisionAbstrak. Untuk mendukung kegiatan operasinya, IEC mengelola empat kamp yang sebagian besar fasilitasnya membutuhkan perbaikan, terutama kompleks perumahan. Rumah kosong dengan kondisi baik hanya tersedia dalam jumlah yang sangat terbatas dan tidak cukup untuk memenuhi semua permintaan perumahan yang ada. Di saat yang bersamaan, kondisi bisnis saat ini memaksa perusahaan untuk mengurangi biaya operasional untuk pemeliharaan bangunan. Terbatasnya jumlah rumah yang kosong, terbatasnya anggaran untuk pemeliharaan bangunan dan tingginya jumlah permintaan rumah telah menciptakan daftar antrian panjang dan backlog yang tinggi pada daftar penempatan perumahan. Penelitian ini bertujuan untuk melakukan analisis pada proses penyediaan perumahan saat ini yang memiliki backlog tinggi dalam daftar penempatan perumahan dan untuk mengusulkan intervensi untuk memperbaikinya. Kombinasi metodologi DMAIC (Define, Measure, Analyze, Improve, Control) dan Analisis Keputusan akan digunakan untuk mengeksplorasi dan memecahkan masalah ini, Berdasarkan analisa yang dilakukan, akar dari masalah ini adalah tidak adanya alat prioritisasi yang layak, tidak adanya personil yang bertugas untuk melakukan pekerjaan tersebut dan kebijakan perusahaan yang tidak diperbarui. Oleh karena itu, solusi yang diusulkan untuk mengatasi masalah ini: alat prioritisasi dikembangkan dan ditingkatkan untuk proses renovasi dan penempatan perumahan, seseorang diberi tugas untuk mengelola proses penyediaan perumahan dan kebijakan internal perumahan direvisi dan diperbarui. Sebagai hasilnya, dengan dukungan kuat dari pimpinan perusahaan dan kolaborasi dari tim lintas fungsi, backlog di daftar penempatan perumahan dapat dikurangi menjadi 0 (nol). Namun, perbaikan proses renovasi perumahan masih diperlukan, terutama dalam mengurangi waktu dalam melakukan tugas renovasi.Kata kunci: DMAIC, analisis keputusan, SMART, AHP, penyediaan perumahan